2011
DOI: 10.1002/anie.201100446
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Preformed Three‐Dimensional Photonic Crystals onto Dye‐Sensitized Solar Cells

Abstract: Film star: Preformed self‐assembled 3D photonic crystals (see picture) can be infilled with a polycarbonate matrix for mechanical stability and transferred onto rough and porous optoelectronic and photovoltaic devices. This technique allows the incorporation of photonic crystals onto independently processed devices, in which the transferred films have high optical quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 23 publications
0
110
0
1
Order By: Relevance
“…These methods include, but are not limited to, atomic layer deposition [106][107][108][109], chemical vapor deposition [11,84,108,110], electrochemical deposition [97,[111][112][113][114], and sol-gel techniques ( Figure 8) [85,87,91,93,115,116]. Cai et al demonstrated an improved convective self-assembly technique to fabricate composite heterostructures, and they showed that they could fabricate both opaline and inverse opaline heterostructures with long range ordering (>100 × 100 µm²) [93].…”
Section: Inverse Opalsmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods include, but are not limited to, atomic layer deposition [106][107][108][109], chemical vapor deposition [11,84,108,110], electrochemical deposition [97,[111][112][113][114], and sol-gel techniques ( Figure 8) [85,87,91,93,115,116]. Cai et al demonstrated an improved convective self-assembly technique to fabricate composite heterostructures, and they showed that they could fabricate both opaline and inverse opaline heterostructures with long range ordering (>100 × 100 µm²) [93].…”
Section: Inverse Opalsmentioning
confidence: 99%
“…They concluded that the wavelength selective photonic crystal concentrator can improve the maximum power of the DSSC by more than five times while retaining a stable high performance ( Figure 13) [135]. The use of self-assembled colloidal crystals in dye sensitized solar cells (DSSCs) has also drawn much interest in recent years [106,108,[129][130][131][132][133]. DSSCs are an interesting alternative to conventional solid state semiconductor photovoltaic devices largely due to their low cost of production [134].…”
Section: Photon Management In Photovoltaicsmentioning
confidence: 99%
“…This gives photons a higher probability of being absorbed in this layer, 77 -79 improving an effi ciency that is limited, in part, because the organic dyes used in DSSCs are poor absorbers of red and near-infrared light. 80 Mihi et al 78 increased DSSC power effi ciency by using a porous PhC coupled to the working electrode. Guldin et al 79 achieved similar results by fabricating a double-layer DSSC using titania inverse opals and mesoscopic block-copolymer-patterned titania.…”
Section: Electrochemical Devices Based On 3d Architecturesmentioning
confidence: 99%
“…This feature is derogated by reducing film thickness in thin-film solar cells such as dye sensitized solar cell (DSSC); therefore, many approaches are made to improve it. For example, porous active layer with high surface area [1][2][3], hierarchically nanostructures as photoanode [4][5][6], scattering layers on the top of active film [7][8][9], plasmonic photoanodes [10][11][12] and photonic crystal photoanodes [13][14][15] have been applied for changing the optical design of the DSSC to optimize its light absorbance. Since the mentioned approaches have some limitations like high reflectance loss and low dye adsorption, researchers are still extensively eager to explore the new light trapping structures as photoanode.…”
Section: Introductionmentioning
confidence: 99%